A DEFICIÊNCIA FÍSICA NAS REVISTAS VEJA, ÉPOCA E ISTOÉ: um estudo de recepção - Mavignier, Tancy Costa (2013)
Most research on media and disability studies how disabled people are represented by journalism. The representations as found by researchers are those of welfarism, standardization, overcoming and citizenship. This study seeks to understand the perception of people with disabilities on news magazines and find out how they feel represented by such media. We worked with three news magazines: Veja, Época and Istoé. To build the corpus of the research were selected texts on disability issues in the time period from July to December 2012, during which occurred the Paralympics Games and dates related to campaigns of disabled people. Regarding methodological procedures, at first a content analysis was made. Then rhetorical analysis of discourse of three journalistic texts were chosen, one from each journal, according to the prevailing representation. Finally we made a study of reception, with 16 respondents, half of them of students at the Methodist University of São Paulo and the other portion of Apart patients (Association of Paraplegics of the Taubaté city, Brazil). The analysis revealed that the representation that appeared over this period was that of overcoming, but that people who have physical disabilities want to be better represented, that is in a more humane and inclusive way.